Optimization of Bali Tourism Recommendations Based on Personal Motivation of Tourists Using the Naive Bayes Algorithm - Putra, I Gusti Ngurah Agung Widiaksa; Arya Kadyanan, I Gusti Agung Gede; Gede Dwidasmara, Ida Bagus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 10 No 1 (2021): JELIKU Volume 10 No 1, Agustus 2021, 2021)
In the recovery of the tourism sector in Bali due to COVID-19, a solution is needed with the aim of making tourists more interested in having a vacation in Bali. One of the solutions that can be offered is optimizing the tourist recommendations on the island of Bali, because so far tourists only get travel recommendations from travel agents and guides who usually recommend favorite tourist destinations, and sometimes guides recommend tourist attractions according to their personal wishes or goals. making tourists less optimal in enjoying tourist attractions in Bali. Optimization of Bali Tourism Recommendations Based on Tourist Personal Motivation Using the Naive Bayes Algorithm, is one solution to optimize tourism recommendations in Bali, where tourist recommendations are taken based on tourist characteristics using the Naïve Bayes Algorithm. In this study the authors used 180 training data, and the results of this study indicate that the personal motivation of tourists who are processed using the Naïve Bayes algorithm is feasible to use for tourism recommendations in Bali. Keywords: Recommendation Optimization, Personal Motivation, Naïve Bayes.